Inter-individual similarities and variations in muscle forces acting on the ankle joint during gait - Błażkiewicz, Michalina; Wiszomirska, Ida; Kaczmarczyk, Katarzyna; Naemi, Roozbeh; Wit, Andrzej (Gait & posture, 2017)
•Maximum-peaks of individual ankle muscles forces during gait is found.•Variation in maximum-peaks of ankle muscle force across subjects was demonstrated.•The order over which the muscles are sorted was determined. Muscle forces acting over the ankle joint play an important role in the forward progression of the body during gait. Yet despite the importance of ankle muscle forces, direct in-vivo measurements are neither possible nor practical. This makes musculoskeletal simulation useful as an indirect technique to quantify the muscle forces at work during locomotion. The purpose of this study was to: 1) identify the maximum peaks of individual ankle muscle forces during gait; 2) investigate the order over which the muscles are sorted based on their maximum peak force. Three-dimensional kinematics and ground reaction forces were measured during the gait of 10 healthy subjects, and the data so obtained were input into the musculoskeletal model distributed with the OpenSim software. In all 10 individuals we observed that the soleus muscle generated the greatest strength both in dynamic (1856.1N) and isometric (3549N) conditions, followed by the gastrocnemius in dynamic conditions (1232.5N). For all other muscles, however, the sequence looks different across subjects, so the k-means clustering method was used to obtain one main order over which the muscles’ peak-forces are sorted. The results indicate a common theme, with some variations in the maximum peaks of ankle muscle force across subjects.